The FDA “Black Box” Warning on Antidepressant Suicide Risk in Young Adults: More Harm Than Benefits? - Fornaro, Michele; Anastasia, Annalisa; Valchera, Alessandro; Carano, Alessandro; Orsolini, Laura; Vellante, Federica; Rapini, Gabriella; Olivieri, Luigi; Di Natale, Serena; Perna, Giampaolo; Martinotti, Giovanni; Di Giannantonio, Massimo; et al. (Frontiers in Psychiatry, 2019)
The decision made in the year 2004 by the U.S. Food and Drug Administration (FDA) to require a boxed warning on antidepressants regarding the risk of suicidality in young adults still represents a matter of controversy. The FDA warning was grounded on industry-sponsored trials carried one decade ago or earlier. However, within the past decade, an increasing number of reports have questioned the actual validity of the FDA warning, especially considering a decline in the prescription of the antidepressant drugs associated with an increase in the rate of suicidal events among people with severe depression. The present report provides an overview of the FDA black box warning, also documenting two Major Depressive Disorder patients whose refusal to undergo a pharmacological antidepressant treatment possibly led to an increased risk for suicidal behaviors. The concerns raised by the FDA black box warning need to be considered in real-world clinical practice, stating the associated clinical and public health implications.